2018
DOI: 10.1093/ndt/gfy375
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity shockwave therapy in the treatment of diabetic nephropathy: a prospective Phase 1 study

Abstract: Background Low-intensity shockwave therapy (LI-SWT) is suggested as a therapy for promoting tissue regeneration. In pigs, it was recently found that LI-SWT improved renal function after ischaemic injury. Our objectives were to study glomerular filtration rate (GFR) and albuminuria in diabetic nephropathy (DN) after treatment with LI-SWT. The present pilot study reports on the clinical safety of LI-SWT in DN. Methods A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…This study suggests that low-energy ESWT is a novel noninvasive and effective treatment of DN. “Low-Intensity Shock Wave Therapy in the Treatment of Diabetic Nephropathy: A Prospective Phase 1 Study” by Skov-Jeppesen et al have results that did not demonstrate significant improvements of GFR and albuminuria [29]. The therapeutic effects were not as significant in the prospective phase 1 study by Skov-Jeppesen et al as those in the present study, the possible causes are different therapeutic settings including energy levels, number of shots, and frequency of treatment (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that low-energy ESWT is a novel noninvasive and effective treatment of DN. “Low-Intensity Shock Wave Therapy in the Treatment of Diabetic Nephropathy: A Prospective Phase 1 Study” by Skov-Jeppesen et al have results that did not demonstrate significant improvements of GFR and albuminuria [29]. The therapeutic effects were not as significant in the prospective phase 1 study by Skov-Jeppesen et al as those in the present study, the possible causes are different therapeutic settings including energy levels, number of shots, and frequency of treatment (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the side effects to LI-ESWT were comparable to our previous report. 25 In summary, LI-ESWT is clinically and biochemically safe in human diabetic kidney disease.…”
Section: Discussionmentioning
confidence: 96%
“…Preliminary results from the present trial were published in a safety report. 25 In the present analysis, the results were reported for a total of 28 patients. Only 14 patients were included in our preliminary safety report.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Importantly, this novel therapy does not cause detectable kidney injury in normal pigs, underscoring its safety (54). A recent pilot study in patients with diabetic nephropathy reported safety of SW therapy in human kidneys as well (58). Further studies are needed to define the optimal regimen of SW treatment in the ischemic kidney.…”
Section: Therapies To Restore the Renal Microcirculationmentioning
confidence: 95%